Pengaruh Kepuasan Kerja Terhadap Tingkat Intensi Turnover Karyawan PT. Majuperkasa Indonesia - Gusti Akhmad Adam (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Human resources (HR) is one of the main organizational capital that can encourage other resources, therefore the success of a company or organization is highly dependent on the quality of human resources in the organization. In developing a company or organization, it cannot be separated from the problem of employee turnover intention. One of the influences on turnover intention is job satisfaction in employees. In this study, the effect of job satisfaction is further investigated to determine whether employee job satisfaction affects employee turnover intention. The research design used is non-experimental quantitative with survey method. The participants of this study amounted to 65 people and data collection was carried out online with purposive sampling technique and the data were processed using simple linear regression analysis. The results of the analysis showed a significant negative influence, meaning that the higher the job satisfaction will have a significant effect on the lower the turnover intention.It is hoped that the results of this research can have implications for PT. Majuperkasa Indonesia to make efforts to increase job satisfaction, such as providing clear compensation, rewards and punishment.